İstanbul’un Tarihi ve Kültürel Değerleri Kapsamında Arz Sağlayıcılar Perspektifinden Destinasyon İmajının Değerlendirilmesi ve Analizi / Destination Image Evaluation and Analysis from the Suppliers’ Perspective within the scope of Historical and Cultural Values of Istanbul - Yamaç Erdoğan, Zeynep; Zengin, Burhanettin (Journal of History Culture and Art Research, 2019)
Abstract Istanbul is an attraction centre as a destination providing unique experiences for tourists by holding historical and cultural resources. In order to maintain the position as an attraction centre, one of the key elements is favourable destination image. The study aims to reveal that how tourists perceive destination image of İstanbul and how this reflects on marketing efforts from the standpoint of one of the contributory stakeholders on shaping destination image, marketing managers of the hotels. Interviewing technique is used to obtain data within the qualitative study. Accordingly, face-to-face in-depth interviews are conducted with the marketing managers of five-star hotels -operating in Istanbul-, the obtained data is analysed and interpreted by using computer-aided qualitative data analysis programme “MAXQDA”. Results revealed that destination image of Istanbul was negatively affected due to security based problems in 2016, however, it has been recovering since last two years and showing significantly positive-orientation. For the future, the marketing managers estimate that destination image of Istanbul will be favourable. In this direction; bringing continuity to the organizations becoming brands with the name of Istanbul by adopting a global approach for advertising and promotion efforts, exploring and developing alternate operating areas by following new opportunities as health tourism and Indian market that is coming into prominence especially with wedding organizations are stated as some of the important steps to be taken. Öz İstanbul, sahip olduğu tarihi ve kültürel kaynaklar bağlamında turistlere eşsiz deneyimler sunan bir destinasyon olarak yüzlerce yıldır cazibe merkezi konumundadır. Söz konusu cazibenin sürdürülebilmesi, destinasyon imajının olumlu olması ile de doğrudan ilişkilidir. Bu çalışmada destinasyon imajının şekillendirilmesinde rol oynayan paydaşlardan biri olan otellerin pazarlama yöneticilerinin nezdinde, turistlerin İstanbul destinasyonunun imajını nasıl algıladığını ve bunun pazarlama çalışmalarına nasıl yansıdığını ortaya çıkarmak amaçlanmıştır. Nitel bir çalışma olarak tasarlanan bu çalışma için veri toplamada görüşme tekniğinden yararlanılmıştır. Bu doğrultuda İstanbul’da faaliyet gösteren 40 adet beş yıldızlı otel işletmesinin pazarlama yöneticileri ile yüz yüze görüşülerek mülakat yapılmış, elde edilen veriler bilgisayar destekli nitel veri analizi programı “MAXQDA” kullanılarak analiz edilmiş ve yorumlanmıştır. Elde edilen sonuçlara göre; İstanbul destinasyonu imajının 2016 yılında güvenlik temelli sorunlardan dolayı negatif etkilendiği, son iki yılda pozitif yönelimli olarak olumluya doğru gitmekte olduğu ortaya çıkmıştır. Gelecekte ise pazarlama yöneticileri tarafından İstanbul destinasyonu imajının olumlu olacağı tahmin edilmektedir. Bu doğrultuda yapılması gerekenler; tanıtım ve reklam çalışmalarında küresel bir yaklaşım benimseyerek İstanbul’un adıyla markalaşacak organizasyonlara süreklilik kazandırmak, sağlık turizmi ve özellikle düğün organizasyonlarıyla ön plana çıkan Hint pazarı gibi yeni fırsatlara yönelerek alternatif faaliyet alanları keşfetmek ve geliştirmektir.